2016
DOI: 10.1038/bmt.2016.194
|View full text |Cite
|
Sign up to set email alerts
|

Multi-center analysis of the effect of T-cell acute lymphoblastic leukemia subtype and minimal residual disease on allogeneic stem cell transplantation outcomes

Abstract: This study aims to provide a detailed analysis of allogeneic stem cell transplantation (allo-SCT) outcomes in a large T-cell acute lymphoblastic leukemia (T-ALL) cohort with a specific emphasis on the effects of pre-transplant minimal residual disease (MRD) and disease subtype, including the aggressive early-thymic precursor (ETP) subtype. Data from 102 allo-SCT patients with a diagnosis of T-ALL from three centers were retrospectively analyzed. Patients were grouped into four T-ALL subtypes: ETP, early, corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 32 publications
5
48
0
Order By: Relevance
“…In our large contemporary cohort of T-ALL patients undergoing allogeneic HCT, including recipients of an RIC regimen and alternative donor HCT, one-third of the patients with high-risk disease survived for more than 5 years; however, relapse was the major cause of treatment failure. These data also identify disease status at transplantation as the most important risk factor for survival, confirming previous studies demonstrating the prognostic significance of achieving CR at the time of transplantation [46]. A single-institution study evaluated 53 patients with high risk T-ALL who underwent allogeneic HCT [4].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In our large contemporary cohort of T-ALL patients undergoing allogeneic HCT, including recipients of an RIC regimen and alternative donor HCT, one-third of the patients with high-risk disease survived for more than 5 years; however, relapse was the major cause of treatment failure. These data also identify disease status at transplantation as the most important risk factor for survival, confirming previous studies demonstrating the prognostic significance of achieving CR at the time of transplantation [46]. A single-institution study evaluated 53 patients with high risk T-ALL who underwent allogeneic HCT [4].…”
Section: Discussionsupporting
confidence: 79%
“…A recent study reported by Brammer et al [6] found that the presence of minimal residual disease (MRD) at the time of HCT is highly predictive of relapse. Although we did not have information on MRD status at HCT, future studies will need to consider its impact on transplantation outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of MRD is usually associated with an increased risk of disease recurrence and worse outcome [22]. Relative to MRD-negative patients, MRD-positive patients in CR1 undergoing allo-HSCT had a significantly worse outcome with a 3-year cumulative incidence of relapse that approximated 60% to 76%, resulting in an estimated survival of approximately 20% to 30%, with MRD being the dominant risk factor for adverse outcomes [8,23,24]. Because these outcomes with current approaches to allo-HSCT for MRD-positive CR patients are unsatisfactory, it is appealing to consider treatment intensifications during induction/postremission therapy and/or before transplantation in an attempt to induce an MRD negative state [25].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, every effort should be made to cure T cell ALL with active frontline therapies, and early referral for alloHCT should be emphasized for high-risk features based on genetics, MRD response and possibly phenotype (early thymic T cell). In a retrospective analysis, alloHCT produced a 3-year OS of 62% for adults with T cell ALL in first CR, and no difference in outcomes was noted on the basis of leukemia phenotype (early thymic vs. others) [143].…”
Section: Cd20 Antibodies (Rituximab Ofatumumab)mentioning
confidence: 99%